FRI0667 Development and validation of a rheumatologist satisfaction with practice scale– "the rheumatologist satisfaction scale" (RSS). (12th June 2018) - Sheth, K.; Valenzuela, A.; Shoor, S.; Ritter, P.; Lorig, K.
Abstract : Background: Rheumatology practice improvement research routinely measures patient satisfaction and disease-specific outcomes but seldom considers the satisfaction of physicians who deliver the care. Studies suggest that physician dissatisfaction may pose a barrier to implementing quality improvement efforts. There is a paucity of succinct measures of physician satisfaction. Objectives: As part of a Performance Improvement Project, in an academic rheumatology practice and an affiliated practice, we developed and piloted a simple questionnaire to study physician satisfaction in Rheumatology. Methods: Thirty-five rheumatologists in the academic or private setting were sent opened-ended questions to determine the factors that made them satisfied or dissatisfied with respect to their rheumatology practice. From the responses we formed 14 questions on a 0 to 10 scale centering on satisfaction and dissatisfaction. We then administered the questionnaires to a small pilot of 30 rheumatologists in academic and/or private setting. Results: Our sample included 30 rheumatologists, from whom 60% were faculty members, 27 % were fellows. 53% (N=16) were males and the majority (77%) were salaried. Racial distribution was 57% white, 40% Asian, with 7% Hispanic/Latino ethnicity. The most common practice setting was academic medicine (80%, N=24), followed by multi-specialty group (10%, N=3), private practice (7%, N=2), and rheumatology group (3%, N=1). 40% (N=12) and 37% (N=11) had been in practice <5 and >30 years, respectively. Coefficient Alpha for each factor was 0.54 (raw), 0.66 (standardized) for satisfaction and 0.60 (raw), 0.60 (standardized) for dissatisfaction. Based on the results of this survey, mean satisfaction factor in rheumatologists was high (8.6±0.99). 91.3% of rheumatologists (N=21) had mean satisfaction factor >8 (range 5.5–9.9). The ability to make a difference in patient's life and having the opportunity to work with great colleagues were the strongest contributors to physicians' satisfaction (mean 9.2±1.1 and 9.4±0.8, respectively). Time spent on documentation and getting inappropriate referrals that are not in the scope of practice were among the strongest contributors to physicians' dissatisfaction (mean 3± 1.9 and 3.9±1.3, respectively). None of the items were highly correlated with each other. This work has now been expanded to more than 150 rheumatologists including in the United States(US) and Latin American countries. Analysis is in progress. Conclusions: A simple and practical questionnaire to measure physician satisfaction was developed and successfully piloted on a predominately academic sample of rheumatologists. The strongest correlates of physician satisfaction were the "ability to make a difference in a patient's life" and to "work with great colleagues" whereas the greatest correlates of dissatisfaction were "time spent on documentation" and "inappropriate referrals." With further testing on a larger sample from the US and Latin American countries, we aim to gain a deeper understanding of how the cultural differences and practice of medicine may affect physician satisfaction. It is hoped that, this scale will serve as a means of determining aids and barriers to improving rheumatology practice for both patients and physicians and become a useful tool in rheumatology performance practice implementations and studies. Disclosure of Interest: None declared